Improving reporting of meta‐ethnography: The eMERGe reporting guidance. (15th January 2019) - France, Emma F.; Cunningham, Maggie; Ring, Nicola; Uny, Isabelle; Duncan, Edward AS; Jepson, Ruth G; Maxwell, Margaret; Roberts, Rachel J.; Turley, Ruth L.; Booth, Andrew; Britten, Nicky; Flemming, Kate; et al.
Abstract: Aims: The aim of this study was to provide guidance to improve the completeness and clarity of meta‐ethnography reporting. Background: Evidence‐based policy and practice require robust evidence syntheses which can further understanding of people's experiences and associated social processes. Meta‐ethnography is a rigorous seven‐phase qualitative evidence synthesis methodology, developed by Noblit and Hare. Meta‐ethnography is used widely in health research, but reporting is often poor quality and this discourages trust in and use of its findings. Meta‐ethnography reporting guidance is needed to improve reporting quality. Design: The eMERGe study used a rigorous mixed‐methods design and evidence‐based methods to develop the novel reporting guidance and explanatory notes. Methods: The study, conducted from 2015 ‐ 2017, comprised of: (1) a methodological systematic review of guidance for meta‐ethnography conduct and reporting; (2) a review and audit of published meta‐ethnographies to identify good practice principles; (3) international, multidisciplinary consensus‐building processes to agree guidance content; (4) innovative development of the guidance and explanatory notes. Findings: Recommendations and good practice for all seven phases of meta‐ethnography conduct and reporting were newly identified leading to 19 reporting criteria and accompanying detailed guidance. Conclusion: The bespoke eMERGe Reporting Guidance, which incorporates new methodological developments and advances the methodology, can help researchers to report the important aspects of meta‐ethnography. Use of the guidance should raise reporting quality. Better reporting could make assessments of confidence in the findings more robust and increase use of meta‐ethnography outputs to improve practice, policy, and service user outcomes in health and other fields. This is the first tailored reporting guideline for meta‐ethnography. This article is being simultaneously published in the following journals: Journal of Advanced Nursing, Psycho‐oncology, Review of Education, and BMC Medical Research Methodology . Abstract : 目的: 本研究的目的是为提高元人种志报告的完整性和清晰度提供指导。 背景: 基于证据的政策和实践需要强有力的证据合成, 以进一步了解人们的经验和相关的社会过程。 种志是由诺伯特和黑尔开发的一种严谨的七‐相定性证据综合方法。元人种志在健康研究中被广泛使用, 但报告质量往往很差, 这阻碍了对研究结果的信任和使用。元人种志报告指南是提高报告质量所必需的。 设计: 本研究采用了严格的混合方法设计和基于证据的方法来开发新的报告指南和注释。 方法: 这项研究从2015年到2017年进行, 包括:(1)对元人种志行为和报告指南的方法系统审查;(2)审查和审计已出版的元人种志, 以确定良好的实践原则;(3)国际、多学科的共识——建立过程以达成指导内容;(4)创新发展的指导和说明。 研究发现: 新确定的所有七个元人种志实施和报告阶段的建议和良好做法提供了19项报告准则, 并附有详细的指南。 结论: 定制的新兴报告指南, 包含了新的方法论的发展和进步, 可以帮助研究人员报告元人种志的重要方面。使用指南应提高报告质量。更好的报告可以使对调查结果的信心评估更加可靠, 并增加对元人种学输出的使用, 以改进卫生和其他领域的实践、政策和服务用户结果。这是第一个为元人种学量身定制的报告指南。本文同时发表于《高级护理杂志》、《精神肿瘤学》、《教育评论》和《英国医学委员会医学研究方法论》等期刊。